Big Ideas in primary mathematics: issues and directions - Askew, Mike (Faculty of Education, University of the Free State, 2013)
This article is located within the literature arguing for attention to Big Ideas in teaching and learning mathematics for understanding. The focus is on surveying the literature of Big Ideas and clarifying what might constitute Big Ideas in the primary Mathematics Curriculum based on both theoretical and pragmatic considerations. This is complemented by an analysis of the evidence for two Big Ideas in South Africa’s Curriculum and Assessment Policy Statements for Foundation- and Intermediate- Phase Mathematics. This analysis reveals that, while there is some evidence of implicit attention to Big Ideas in the Curriculum, without more explicit attention to these, teachers and, consequently, learners are not likely to develop understanding of Big Ideas and how they connect aspects of mathematics together.
Keywords: Primary mathematics; Big ideas; CAPS; Foundation; Intermediate; Curriculum; South Africa